Plastid-Localized EMB2726 Is Involved in Chloroplast Biogenesis and Early Embryo Development in Arabidopsis - Li, Chuanling; Shang, Jian-Xiu; Qiu, Chenlei; Zhang, Baowen; Wang, Jinxue; Wang, Shuo; Sun, Yu (Frontiers in Plant Science, 2021)
Embryogenesis is a critical developmental process for higher plant to establish the body organization. During this process, the biogenesis of chloroplasts from proplastid is essential. Failure in chloroplast development during embryogenesis could produce a morphologically abnormal embryo or even embryonic lethal. will lead to abnormally developed embryo and in many times embryo lethal. In this study, we isolated a T-DNA insertion mutant on Arabidopsis gene EMBRYO DEFECTIVE 2726 (EMB2726). The emb2726 heterozygote seedlings produced about 25% albino ovulesseeds with embryos display obvious phenotype at the 32-cell stage and arrested inat the late globular stage. EMB2726 protein was localized in the chloroplast and expressed in all stages of plant development, including embryogenesis; and the two translation elongation factor Ts domains within the protein were critical for its function. Using transmission electron microscopy, we found that the cells in emb2726-/- embryos only contained undifferentiated proplastids and the expressions of plastid genome encoded photosynthesis -related genes were dramatically reduced. The expression studies of DR5::GFP, pDRN::DRN-GFP, and pPIN1::PIN1-GFP reporter lines indicated the auxin biosynthesis was normal but polar auxin transport was affected. The expression of pSHR::SHR-GFP and pSCR::SCR-GFP confirmed the procambium and ground tissue precursor were not initiated in emb2726-/- embryo. Our results suggest that EMB2726 plays a critical role during Arabidopsis embryogenesis by affecting chloroplast development possibly through affecting plastid translation process.